2021
DOI: 10.1017/s1092852921000043
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of dose–response with asenapine: a cluster analysis of randomized, double-blind, and placebo control study

Abstract: Background Differences in psychiatric background and dose–response to asenapine in patients with schizophrenia were examined based on efficacy and safety, using data obtained in a double-blind, placebo-controlled trial. Methods Patients with schizophrenia were classified into three clusters by a cluster analysis based on the Positive and Negative Symptom Scale (PANSS) subscores at baseline, using the data from a 6-week, double-blind, placebo-controlled trial. PANSS Marder factor scores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…required a dose of 20 mg/day. 9 These findings, based on short-term results, are consistent with the findings of this survey after 1 year of maintenance treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…required a dose of 20 mg/day. 9 These findings, based on short-term results, are consistent with the findings of this survey after 1 year of maintenance treatment.…”
Section: Discussionsupporting
confidence: 89%
“…A meta‐analysis of short‐term studies in patients with acute‐phase schizophrenia revealed that the effective asenapine dose for 95% of the population was 14.97 mg/day 3 . Furthermore, in a post hoc analysis of a 6‐week RCT in patients with an acute exacerbation of schizophrenia, a cluster analysis based on PANSS Marder factor scores of patients receiving asenapine suggested that some patients required a dose of 20 mg/day 9 . These findings, based on short‐term results, are consistent with the findings of this survey after 1 year of maintenance treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The reported patients were all treated with asenapine 20 mg; the chlorpromazine equivalent- dose is 800 mg. Our present two patients’ symptoms were also successfully controlled with similar dose of asenapine. According to a recent sub-analysis of a clinical trial [ 26 ], a portion of patients with schizophrenia respond further to the higher dose (20 mg) of asenapine, which might also be the case for our patients. In addition, both of our patients showed EPS and hyperprolactinemia, which are common adverse effects of serotonin-dopamine antagonists.…”
Section: Discussionmentioning
confidence: 75%
“…The PANSS five-factor model has previously been used to analyze the results of phase 3 studies comparing the efficacy of SLA 5 mg and 10 mg BID vs placebo in patients with acute schizophrenia. 16 , 18 Dose equivalencies for SLA 5 mg and 10 mg BID are HP-3070 3.8mg/24h and 7.6mg/24h, respectively. 19 Kane et al 16 reported that after 6 weeks of treatment, both studied doses of SLA were superior to placebo on the PANSS positive symptoms domain and SLA 5 mg was superior to placebo on the anxiety/depression and disorganized thought factors, but SLA was not superior to placebo on negative symptom and hostility/excitement factors.…”
Section: Discussionmentioning
confidence: 99%